(untitled) - Verma, Ashok (Harrow, U.K, 2005)
The book provides major topics related with various invertebrates groups starting from Protozoa to Echinodermata, emphasizing their structure, function and adaptations. It deals with important features like osmoregulation, nutrition, locomotion, reproduction of protozoa including disease producing protozoa, the amazing phenomenon of polymorphism and alternation of generation in coelenterates, the wonderful world of corals including their power of defense. The parasitic helminthes, their adaptations to the parasitic mode of life and the plant parasitic nematodes have also been discussed. Minor phyla also find elaborate description. Different aspects of arthropods like parasitism and larval forms in crustaceans, biology of Sacculina, respiration, mouthparts and metamorphic events in insects, including useful insects have also been illustrated. Groups like priapulida, bryozoa and chaetognatha find special mention. The text also includes different aspects of mollusks like torsion, adaptive radiation, foot and shell along with brain and sense organs in cephalopods and symmetry, coelom and larval forms in echinoderms.
Keywords: Invertebrates,Zoology,Động vật không xương sống,Động vật học